Toleransi Kehidupan Beragama Menurut Hukum Islam - Usman Usman; Devi Syukri Azhari (Journal on Education, 2023)
Islam is a religion that regulates human life towards a plenary life. Because Islam is a system of life that is comprehensive and complete and regulates a wise foundation down to the smallest things. So, Islam since its inception (fourteen centuries) has essentially brought teachings that not only discuss one dimension of life, but Islam has brought multi-dimensional teachings of human life, namely the dimensions of theology, worship, muamalah, morals, philosophy, law and so on. Islam is a complete, comprehensive and perfect teaching that regulates the way of life for a Muslim both when worshiping and interacting with his environment. All of these teachings are summarized in the Koran and al-Hadith in the form of both global and technical concepts. Religious tolerance in Islam is an attitude of respecting, allowing, allowing opinions, views, beliefs, habits, behavior, and so on that differ from behavior that follows the rules of each religion, where people always respect, respect the behavior of others. because tolerance in Islam means highly appreciating attitudes and actions that prohibit discrimination against other people who are different in a society. Islam is a religion that teaches humanity to always respect and tolerate others and maintain the sanctity and truth of Islamic teachings.